My nine lives sixty years in israeli and biblical archaeology. - DEVER, WILLIAM G. (SBL PRESS, 2020)
Experience a lifetime of adventure This autobiography of prominent American archaeologist William G. Dever is unabashedly his story, in which he offers candid, often brutally honest, reflections on his life and sixty-five-year career. Dever places himself in the midst of a remarkable generation of giants in archaeology in Israel during a period when the fields of biblical and Israeli archaeology were evolving. With technical expertise developed over a lifetime of working alongside four generations of Israeli and foreign excavators, he recalls their exploits and shares numerous personal stories that few others would know. His memoir concludes with a postscript on the likely future of biblical archaeology and an annotated bibliography for serious readers who wish to explore some of the scholarly literature to flesh out Dever's narrative.--